Inability of Turbidimetry Method in Detecting Glycated Hemoglobin to Select Diabetes Mellitus Patients According to Their Concentrations of Blood Glucose Levels. Issue 4 (17th August 2014) - Abdallah, Alessandra M.; Alves, Beatriz C. A.; Gehrke, Flávia S.; Sant´Ana, Aleksandra V. L.; Azzalis, Ligia A.; Junqueira, Virginia B. C.; Adami, Fernando; Pereira, Edimar C.; Fonseca, Fernando L. A.
<x xml:space="preserve">Abstract</x> Background Diabetes mellitus is a chronicle illness in which there is a high blood glucose level defined as hyperglycemia, resulted by a deficiency in insulin secretion and/or in its action. Nowadays, it is being seen as a public health problem and is reaching increasing proportions with regard to the appearance of new cases. For diagnosis, sensible and accurate methods should be used to avoid complications of the sickness. The measure of glycated hemoglobin may not be used for diagnosis, but is the reference method to evaluate the grade of glycemic control in the long term, reflecting the blood glucose level in the latest 2–3 months. The aim of this study was to evaluate the grade of concordance between turbidimetry and liquid chromatography methods in the glycated hemoglobin determination and to estimate the sensibility and specificity values of turbidimetry. Methods This study included 133 blood samples obtained from patients and healthy donors, ageing between 18 and 80 years with glycemic values between 58 and 473 mg/dl. Results and Conclusion Turbidimetry is a useful method for determining glycemic levels above 100 and over 200 mg/dl, but does not have the ability to select samples with intermediary blood glucose concentrations.